Association Between Sex-Specific Serum Gamma-Glutamyltransferase and Incidence of Hypertension in a Chinese Population Without Metabolic Syndrome: A Prospective Observational Study - Wu, Xiaoyun; Liang, Dongjie; Sun, Junfang; Lin, Yanyan; Wu, Shengjie (Frontiers in Cardiovascular Medicine, 2021)
Background: Higher serum gamma-glutamyltransferase (GGT) is associated with high risk of hypertension. We aimed to examine the association between sex-specific serum GGT levels and incident of hypertension in a Chinese population without metabolic syndrome. Methods: Participants who were free of hypertension and metabolic syndrome from the First Affiliated Hospital of Wenzhou Medical University between 2009 and 2014 were included. Participants were grouped into sex-specific quartiles of GGT levels (Q1–Q4) defined as: ≤19, 20–26, 27–38, and ≥39 U/L for male; ≤12, 13–15, 16–19, and ≥20 U/L for female. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for incidence of hypertension according to sex-specific quartiles of GGT levels. Kaplan–Meier analysis and interaction analysis were conducted. Results: Among 38,806 participants included (average age 36.0 years, 54.0% men), 4,505 of them developed hypertension. In the overall study population, using Q1 as the reference group, participants in Q2, Q3, and Q4 showed a higher risk of developing hypertension, with HRs (95% CIs) of 1.126 (1.029–1.232), 1.187 (1.083–1.302), and 1.300 (1.182–1.431), respectively (P < 0.001), after adjusting for known confounders. Sex-specific analysis showed that the adjusted HRs for participants in Q4 (reference: Q1) were greater in females [1.321 (1.100–1.586, P < 0.001)] than in males [1.268 (1.133–1.420, P < 0.001)] (P for interaction = 0.047). Moreover, interaction analysis showed that this association was consistently observed when the participants were stratified by age, body mass index, and fatty liver status. Conclusion: Among Chinese adults without metabolic syndrome, serum GGT level was positively associated with incidence of hypertension, and the association was stronger in females than in males.